Die WTO-Verhandlungen und die GAP - Martina Brockmeier; Janine Pelikan; Rainer Klepper (Agrarwirtschaft: Zeitschrift für Betriebswirtschaft, Marktforschung und Agrarpolitik, 2008)
– Over the last decades the EU Common Agricultural Policy (CAP) has been increasingly influenced by the WTO negotiations. The MacSharry-Reform and the Mid Term Review (MTR) reform of the CAP for example improved the conformity between the EU agricultural policy and the liberalization requirements on the international level. Currently, it is again discussed within the Health Check how the EU direct payments will be adapted to meet the international and national requirements. This paper employs the Global Trade Analysis Project (GTAP) Model to quantify the global and national effects of the implementation of the current WTO negotiations and the adaptation of the EU direct payments. The impact of the change in the respective political instruments and the exemption of sensible products are calculated with the help of two policy scenarios and a decomposition and set in relation to each other. This procedure shows that the cut of agricultural tariffs is of considerable importance for almost all commodities in all countries and regions. In contrast, the adaptation of the EU direct payments is only of greater importance for the EU itself.
Keywords: 330; WTO-Recht; Politische Entscheidung; EU-Agrarpolitik; Agrarreform; Agrarsubvention; Wirkungsanalyse; EU-Staaten